In vitro and in silico dynamic analysis of alkaloid extract of Moringa oleifera leaf as a Tocolytic agent - Ofioritse O. Ofulue; Isoken M. Ebomoyi; Adaeze P. Uchendu (Elsevier, 2024)
Background of Study: Tocolytics are substances which prevents preterm births by reducing or stopping uterine contractions. This study is aimed at using both in vitro and in silico docking in investigating Alkaloid extract of Moringa oleifera leaf (AML) as a tocolytic agent. Method: The in vitro study was carried out on isolated uteri of albino wistar rats, a cumulative application of AML and its active fraction; chloroform fraction of AML (CAML) to the isolated uterine tissues was done. Compounds present in CAML were investigated via GC-MS. In the in silico study, compounds present in CAML were docked using the Autodock program to predict the most active compounds and possible binding sites between CAML and some target proteins (OXTR, ERs, COX-1 and TNF-α) associated with uterine contractions and the pharmacokinetic properties of the active compounds identified were investigated using lipinski rule of five (5). Results: In the in vitro study, the result showed that AML and CAML significantly inhibited spontaneous contractions. CAML significantly inhibited oxytocin-induced, KCl-induced and calcium-free solution contractions. In silico study; 6 out of 47 compounds present in CAML had a strong binding affinity for OXTR, ERs, COX-1 and TNF-α and the pharmacokinetic investigation showed that these 6 compounds were likely oral drug candidates. Conclusion: AML and CAML inhibits spontaneous contractions and contain compounds that has the ability to interact with receptors and proteins associated with uterine contractions making it a good tocolytic agent.